Ocena efektywności gospodarowania zakładu opieki zdrowotnej - Karmowska, Grażyna (The Estimation of Healthcare Institution Efficiency, 2009)
The aim of the article is to estimate the efficiency of a healthcare institution with the use of the causative analysis of financial results, but also to establish the most affecting factors. The author uses the quadric factor causative method. Financial results obtained between 2004 and 2005 indicated a positive effect of intensive factors. In 2006 there were not any fulfilled standards for a rational activity. Financial advanced indicators and fluctuation factors show the inability to pay the debts and financial fluctuation threat
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 89-96